CMET-31. WHOLE BRAIN RADIOTHERAPY VERSUS STEREOTACTIC RADIOSURGERY IN POOR-PROGNOSIS PATIENTS WITH 1 – 10 BRAIN METASTASES: A RANDOMIZED FEASIBILITY STUDY. (11th November 2019) - Nichol, Alan; Raman, Srinivas; Mou, Benjamin; Hsu, Fred; Valev, Boris; Cheung, Arthur; Vallières, Isabelle; Beaton, Laura; Rackley, Thomas; Gondara, Lovedeep
Abstract: BACKGROUND: The clinical advantage of stereotactic radiosurgery (SRS) over whole brain radiotherapy (WBRT) in patients with brain metastases and poor prognosis is controversial. To investigate the feasibility of a phase III clinical trial in a population of patients with poor prognosis, we conducted a randomized feasibility study of WBRT versus SRS. METHODS: Patients with Karnofsky performance status (KPS) ≥ 70, life expectancy of 3–6 months, based on both Diagnosis-Specific Graded Prognostic Assessments and attending oncologist opinion, and 1– 10 brain metastases with a diameter ≤ 4 cm were enrolled at six Canadian cancer centers. Patients were randomly assigned to WBRT (20 Gy in 5 fractions) or SRS (15 Gy in 1 fraction). The primary endpoint was the rate of accrual. A secondary endpoint was the ratio of screened subjects to accrued subjects. This trial is registered with ClinicalTrials.gov (NCT02220491). RESULTS: Between January 2015 and November 2017, 210 were screened to enroll 22 patients (9.5 screened/participant) and 20 patients were randomized. The accrual rate was 0.63 patients / month. The most common reasons for exclusion were: estimated median survival outside 3–6 months (n = 40), baseline KPS below 70 (n = 28), and > 10 brain metastases (n = 28). The median survival was 7.0 months. The overall survival was 9.5 months (n = 11) for patients who had subsequent systemic therapy, compared to 3.7 months (n = 9) in patients who had none. In both arms, the cumulative incidence of retreatment with brain radiotherapy was 40%. CONCLUSIONS: Accrual was slow and the median survival was longer than expected, but a randomized trial evaluating WBRT vs SRS in patients with poor prognosis would likely be feasible by enrolling only patients with no remaining systemic therapy options.